2004
DOI: 10.1128/iai.72.11.6211-6220.2004
|View full text |Cite
|
Sign up to set email alerts
|

Passive Immunization of Neonatal Mice againstPneumocystis cariniif. sp.murisEnhances Control of Infection without Stimulating Inflammation

Abstract: Pneumocystis carinii is an opportunistic fungal pathogen that causes life-threatening pneumonia in immunocompromised individuals. Infants appear to be particularly susceptible to infection with Pneumocystis. We have previously shown that there is a significant delay in clearance of the organisms from the lungs of neonatal mice compared to adults. Since alveolar macrophages are the effector cells responsible for killing and clearance of Pneumocystis, we have examined alveolar macrophage activity in neonatal mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 44 publications
2
32
0
Order By: Relevance
“…This delay in lung T cell infiltration is associated with delayed infiltration and activation of macrophages, delayed chemokine and cytokine production, and delayed adhesion molecule upregulation (12,13,(35)(36)(37). We also found that lung mRNA expression of transforming growth factor ␤2 (TGF-␤2) and TGF-␤3 isoforms was upregulated in the uninfected lungs of infant mice, and TGF-␤1 mRNA expression was similar in adult and infant mice (37).…”
supporting
confidence: 51%
“…This delay in lung T cell infiltration is associated with delayed infiltration and activation of macrophages, delayed chemokine and cytokine production, and delayed adhesion molecule upregulation (12,13,(35)(36)(37). We also found that lung mRNA expression of transforming growth factor ␤2 (TGF-␤2) and TGF-␤3 isoforms was upregulated in the uninfected lungs of infant mice, and TGF-␤1 mRNA expression was similar in adult and infant mice (37).…”
supporting
confidence: 51%
“…This may correspond to either activation of the alveolar macrophages or infiltration of monocytes. We and (10,29). However, we did not see differences in expression of major histocompatibility complex class II in alveolar macrophages from SRAKO compared to wild-type mice (data not shown).…”
Section: Resultsmentioning
confidence: 55%
“…Because we made the interesting observation that SRAKO mice may clear P. carinii faster than wild-type mice, we also examined clearance in neonatal SRAKO mice. We previously reported that neonatal mice clear P. carinii much more slowly than adult mice and were interested in whether the clearance could be expedited in the absence of SRA (10,15,16). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Passive treatment with pools of anti-Pneumocystis monoclonal antibodies, including 4F11, has previously been shown to reduce both organism burden and inflammation (34)(35)(36). Therefore, in addition to the antimicrobial effects, the immunoregulatory effects of high-dose intravenous immunoglobulin (IVIG) may provide additional benefit in the treatment of a patient with PcP.…”
Section: Discussionmentioning
confidence: 99%